Chronological age and performance in paralympic powerlifters: differences between sexes, competition, and weight categories - Lopes-Silva, J. P.; Richardson, D.; Franchini, E. (Journal of Science in Sport and Exercise, 2023)
Purpose: We quantified the chronological age and performance of Paralympic powerlifters competing at the elite level in the World Championships (WC) and Paralympic Games (PG), and examined the age-related differences between sexes, weight categories, and competition achievements. Methods: This was a retrospective study involving 3107 athletes who took part in the last eight WC and six PG. Para powerlifters were divided by sex, chronological age, weight category, and competition achievement. Results: Overall, males were older (33 years) and stronger (lifting 168 kg) than female (32 years and lifting 96 kg, respectively) para powerlifters (P < 0.05). Male and female para powerlifters lifted heavier loads in the PG (174 and 103 kg, respectively) than in WC (163 and 93 kg, respectively) and medallists were younger (31 and 30 years for females and males, respectively) than non-medallists (33 and 32 years for females and males, respectively) (P < 0.05). Para powerlifters competing in lighter categories were younger when compared to heavier categories (P < 0.05), but their relative load was heavier compared to heavier competitors (P < 0.05). Conclusion: Our results show that medallists were younger (31 and 30 years) than non-medallists (33 and 32 years) for females and males, respectively.